Izydora z Sewilli "O narodzinach i śmierci świętych ojców": kompozycja traktatu - Krynicka, Tatiana (Vox Patrum, 2020)
Isidore’s work On the Lifes and Deathes of the Fathers contains biographies of outstanding biblical figures from Adam to Titus. According to what has been announced in the titles and in the introduction, the author describes the ancestry (ortus), character, virtues and achievements (vita), circumstances surrounding the death and burial of the heroes (obitus), among which we find patriarchs, judges, kings, prophets, Lord’s apostles and pupils. Most of them are men: except for few heroins (Esther, Judit, Mary, Mother of Jesus), Isidore presents biblical women very superficially. His descriptions tend to praise the heroes demonstrating them as persons worthy of being imitated. Sevillian does not design a homogenuous and binding all over the treatise model of describing the heroes he presents. Due to this the text is varied and pleasant in perception. Isidore familiarizes his reader with the great biblical figures and broadens his Visigothic audience’s world while transferring into it the exotic topography of Holy Land. He seems to be less interested in precise dating of the events he describes. The treatise’s time seems to be the space of mankind’s redemption and salvation, propitious kairos, in which God speaks to a man and a man fulfills His will, colaborating with Lord’s grace and supported by brethren’s assistance.